Same Difference? Low and High Glucosinolate Brassica rapa Varieties Show Similar Responses Upon Feeding by Two Specialist Root Herbivores - Sontowski, Rebekka; Gorringe, Nicola J.; Pencs, Stefanie; Schedl, Andreas; Touw, Axel J.; van Dam, Nicole M. (Frontiers in Plant Science, 2019)
Glucosinolates (GSLs) evolved in Brassicaceae as chemical defenses against herbivores. The GSL content in plants is affected by both abiotic and biotic factors, but also depends on the genetic background on the plant. Since the bitter taste of GSLs can be unfavorable for both livestock and human consumption, several plant varieties with low GSL seed or leaf content have been bred. Accessions with lower GSL levels can be more susceptible to herbivore pests. However, low GSL accessions may quickly increase GSL levels upon herbivore feeding by activating GSL biosynthesis, hydrolysis or transporter genes. To analyze differences in herbivore-induced GSL responses in relation to constitutive GSL levels, we selected four Brassica rapa accessions, containing either low or high root GSL levels. Plants were infested with larvae of the root fly specialists Delia radicum or D. floralis. Root samples were collected after 3, 5 and 7 days. We compared the effect of root herbivore damage on the expression of GSL biosynthesis (CYP79A1, CYP83B2), transporter (GTR1A2, GTR2A2) and GSL hydrolysis genes (PEN2, TGG2) in roots of low and high GSL accessions in conjugation with their GSL levels. We found that roots of high GSL accessions contained higher levels of aliphatic, indole and benzyl GSLs than low GSL accessions. Low and high GSL accessions both upregulated indole GSL synthesis genes upon infestation with root fly larvae, but low GLS accessions responded stronger. Low GSL accessions additionally upregulated the GSL transporter gene expression. In both GSL accessions, only the aliphatic GSL levels significantly increased in the roots upon Delia herbivory. Low GSL accessions did not show a stronger herbivore-induced response than high GSL accessions, which indicate that there is no trade-off among constitutive and induced GSLs.